Pengaruh Penggunaan Media Kotak Matriks Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas XI SMAN 2 Bukit Batu - Hayu, Sri Rah; Adurrahman; Indriati, Mefa; Anggraini, Lilis Marina (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to see the effect of the use of matrix box media on the understanding of mathematical concepts of grade XI students of SMAN 2 Bukit Batu. This study uses an experimental method with the design of Nonequivalent Control Group Design. The population in this study was all students of class XI, and samples were taken by purposive sampling, with one experimental class using matrix box media and one class as a control class using conventional learning. This research instrument is in the form of a test of understanding of mathematical concepts. The data analysis technique was carried out by descriptive statistical data analysis and inferential statistical data analysis using SPSS 23. The results of the descriptive statistical analysis showed that the average ability of students at the time of the pretest was 55.66 for the experimental class and 55.75 for the control class, while the average result of the posttest was 71.50 for the experimental class and 60.31 for the control class. The results of the inferential statistical analysis carried out by the t-test showed a significance value of 0.003<0.05 which stated that there was an influence of the use of matrix box media on the understanding of mathematical concepts for students in grade XI of SMAN 2 Bukit Batu. These findings confirm that the matrix box media not only makes it easier to understand mathematical concepts, but also makes the learning process more active and meaningful.